Judging Personality from a Brief Sample of Behaviour: Detecting where Others Stand on Trait Continua†. Issue 6 (23rd August 2017) - Wu, Wenjie; Sheppard, Elizabeth; Mitchell, Peter
Abstract: Trait inferences occur routinely and rapidly during social interaction, sometimes based on scant or fleeting information. In this research, participants (perceivers) made inferences of targets' big‐five traits after briefly watching or listening to an unfamiliar target (a third party) performing various mundane activities (telling a scripted joke or answering questions about him/herself or reading aloud a paragraph of promotional material). Across three studies, when perceivers judged targets to be either low or high in one or more dimensions of the big‐five traits, they tended to be correct, but they did not tend to be correct when they judged targets as average. Such inferences seemed to vary in effectiveness across different trait dimensions and depending on whether the target's behaviour was presented either in a video with audio, a silent video, or just in an audio track—perceivers generally were less often correct when they judged targets as average in each of the big‐five traits across various information channels (videos with audio, silent videos, and audios). Study 3 replicated these findings in a different culture. We conclude with discussion of the scope and the adaptive value of this trait inferential ability. Copyright © 2017 European Association of Personality Psychology